Conamomum Pierreanum (Gagnep.) Skornick. & A. D. Poulsen (Zingiberaceae), a New Record for the Flora of Vietnam - Ngoc Anh, Luu Dam; Huong, Bui Van; Truong, Do Van; Cu, Luu Dam; Hai, Do Van; Hung, Nguyen Quang; Thanh, Trinh Xuan; Nguyen, Thanh Trung (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 2, 2021)
Conamomum pierreanum (Gagnep.) Skornick. & A. D. Poulsen, (Zingiberaceae), a previously known species from Thailand and Cambodia, is here reported, as a new record for Vietnam. It is similar to C. rubidum and C. odorum but differs in having a present stilt root; a shorter petiole, 2-3 cm; a larger leaf blade, oblong, 30-50 × 5-8 cm, glabrous; a globose to ovoid inflorescence, arising near the base of rhizome; tomentose outer surface of bract; a 3-toothed bracteole, outer surface hairy; and a smaller filament, yellowish and glabrous. The detailed morphological description, distribution and ecology information, conservation status and a colour plate of this species are given.